Secondary Subacromial Impingement after Valgus Closing-Wedge Osteotomy for Proximal Humerus Varus - Hirotaka Sano; Masayuki Kamimura; Akira Oizumi; Shuji Isefuku (Case Reports in Orthopedics)
A 31-year-old construction worker had been suffering from both the motion pain and the restriction of elevation in his right shoulder due to severe varus deformity of humeral neck, which occurred after proximal humeral fracture. The angle for shoulder flexion and abduction was restricted to 50 and 80 degrees, respectively. Valgus closing-wedge osteotomy followed by the internal fixation using a locking plate was carried out at 12 months after injury. Postoperatively, the head-shaft angle of the humerus improved from 65 to 138 degrees. Active flexion and abduction angles improved from 80 to 135 degrees and from 50 to 135 degrees, respectively. However, the patient complained from a sharp pain with a clicking sound during shoulder abduction even after removal of the locking plate. Since subacromial steroid injection temporarily relieved his shoulder pain, we assumed that the secondary subacromial impingement was provoked after osteotomy. Thus, arthroscopic subacromial decompression was carried out at 27 months after the initial operation, which finally relieved his symptoms. In the valgus closing-wedge osteotomy, surgeons should pay attention to the condition of subacromial space to avoid causing the secondary subacromial impingement.